Analisa Respon Mekanis Bahan Fiber Plastik Jok dengan Metode Uji Tarik (Tensile Test) - Anggri Abdi Rullah; Ade Irwan; Fadly Ahmad Kurniawan Nasution (JITEKH, 2023)
Plastic Fiber Upholstery Is a component that plays an important role for comfort and safety for motorcycle riders, the shape of the seat plastic fiber is also different according to the needs of motorcycles both in terms of type and type. Functions of Plastic Fiber Upholstery seats to support weight and shock absorbers. And here the researcher wants to know the strength of the Plastic Fiber Upholstery using the Tensile test method. Tensile testing is one such test. The method used in this research is a tensile test method using a UTM machine. Material testing machine with a length of 104 mm using ASTM E8. The results of this study have 5 specimens for the first specimen on Fiber Plastic Upholstery has a tensile stress with a value of 33.50 MPa, strain with a value of 0.03. And the modulus of elasticity with a value of 1,176.6 MPa. The second specimen on Plastic Fiber Upholstery had a tensile stress of 30.55 MPa, a strain with a value of 0.02. And the modulus of elasticity with a value of 1.527.5 MPa. The third specimen on Plastic Fiber Upholstery has a tensile stress of 51.60 MPa, a strain of 0.06. And the modulus of elasticity with a value of 860 MPa. The fourth specimen on Plastic Fiber Upholstery has a tensile stress of 19.01 MPa, a strain of 0.02. And the modulus of elasticity with a value of 950.5 MPa. The fifth specimen on Fiber Plastic Upholstery has a tensile stress of 44.81 MPa, a strain of 0.03. And the modulus of elasticity with a value of 1493.6 MPa.